FACTORS INFLUENCE CUSTOMERS PURCHASE INTENTION TOWARDS HYPERMARKETS AT KOTA BHARU, KELANTAN - Man Hong Lu; Muhammad Azim Abu Hassan Sha’ari; Darshini Annamalai; Muhammad Syahril Amin Bin Norazmi; Nurul Asikin Binti Hizani; King Kiat Tan (Jurnal Manajemen dan Kewirausahaan, 2021)
The study's goal was to look into the relationship between price, product quality, and interior atmosphere and customers' purchasing intentions in the Kota Bharu, Kelantan area. Kota Bharu Mall, Aeon, Billion, Tesco, Mydin, Giant, and Pantai Timur Hypermarket were among the hypermarkets studied. Furthermore, this study was carried out to establish what the most influential variables are that which affect consumers' buying intentions and, as a result, how they choose their favourite hypermarket. The independent variables in this study were price, product quality, and interior atmospheric, while the dependent variable was purchasing intention. In this research, a questionnaire survey was used to collect data from customers at seven hypermarkets in Kota Bharu. A total of 417 accurate and usable questionnaires were collected, with responses reported on a four-point Likert-type scale, with one indicating strong disagreement and four indicating strong agreement. All of the independent variables were found to be strongly related to the dependent variables in the sample. Product quality has the highest positive correlation with purchasing intention following by Interior atmospheric and price came in second and third. This demonstrates that even minor changes in all of the independent variables have an impact on purchasing intent.